Antibacterial Activity of Carica papaya against Methicillin resistant Staphylococcus epidermidis Isolated from Wards Surfaces of Kampala International University Teaching Hospital, Bushenyi, Uganda - Sunusi Adam, Abubakar; Ntulume, Ibrahim; Adeyemo, Rasheed; Akinola, Saheed; Jatau Abubakar, Ibrahim; Almustapha Aleiro, Adamu; Onkobah, Sarah; Micheni, Lisa; Namatovu, Alice (Current Trends in Biotechnology and Pharmacy, 2019)
This study aimed at determining the antibacterial activity of Carica papaya against Methicillin resistant Staphylococcus epidermidis isolated from doorknobs, bed rails, floors and walls of Surgical, Medical, Maternity, Pediatrics, Accident and Emergency, Semiprivate and Private wards of Kampala International University Teaching Hospital. The bacteria were isolated from the wards surfaces and identified using biochemical tests, Desferroxiomine and Fosfomycin antibiotics. Disc diffusion method was used to detect methicillin resistance in S. epidermidis using Cefoxitin (30 μg) disc. Fresh leaves and seeds of C. papaya was processed and extracted using standard methods. Antibacterial activities of the methanol, acetone and aqueous crude extracts were assayed using the agar well diffusion method. Phytochemical analysis, Minimum Inhibitory and Bactericidal concentration of the crude extracts were determined using broth dilution methods. Both C. papaya leaf and seed crude extract exhibited antibacterial activity against MRSE with MICs and MBCs ranges of 250 to 31.3mg/ml and 125 to 31.3 mg/mL for leaf and seed extracts respectively. This study concludes that C. papaya leaf and seed crude extracts were effective against Methicillin resistant S. epidermidis.
Keywords: Antibacterial Activity; Carica papaya; Methicillin; Staphylococcus epidermidis; Kampala International University Teaching Hospital